Karakteristik Low Back Pain - Nur Afifah Nazaruddin; Hermiaty Nasaruddin; Mardiana, Mardiana (Lembaga Pengembangan Kinerja Dosen, 2025)
Low Back Pain (LBP) is one of the most common musculoskeletal problems experienced by people in various age groups and work backgrounds. This complaint can be acute, subacute, or chronic, with various causes ranging from mechanical, degenerative, to psychosocial factors. This study aims to examine the characteristics of LBP through a literature review of several previous studies that focus on prevalence, risk factors, and their impact on patients' daily lives. The method used is a narrative literature review, with data sources coming from national and international journals, research reports, and academic repositories. The results of the study show that the prevalence of LBP is very high, with a significant percentage of occurrence in the elderly, pregnant women, administrative workers, and individuals with a sedentary lifestyle and non-ergonomic work posture. In addition to age, female gender, non-ideal body mass index, and long work duration, it was also found that psychosocial characteristics such as low social support and high work pressure play a role in triggering or worsening LBP. A study at Ibnu Sina Hospital Makassar showed that most LBP patients were elderly women with acute pain and radiological results showed lumbar spondylosis as the most common diagnosis. The conclusion of this study emphasizes the importance of prevention through ergonomic education, work stress management, and early intervention based on a healthy lifestyle. These findings are expected to be the basis for designing promotive and preventive strategies for high-risk groups.